Analisis Perbandingan Anggaran Biaya Operasional Dan Anggaran Pendapatan Dalam Menilai Kinerja Keuangan Pada PT. Air Manado - Mayangsari Sorongan; Frendy A. O. Pelleng; Joula J. Rogahang (Universitas Sam Ratulangi, 2018)
Conditions to achieve the target of several years identified that the company (PT. AIR Manado) experienced obstacles in the process of actualizing the draft budget that had been prepared by the company. Thus, this study aims : (1). To analyze the difference between the budget and its realization, both the operational budget and the income budget and make comparisons between the two components of the budget; (2). To determine the magnitude of the effect of the operational cost budget and income budget on financial performance at PT. AIR Manado. This research is descriptive-explanatory so it uses descriptive-analytic method with a verivative-quantitative research approach. The result of this study indicate that (1). Based on the determination coefficient value, the operational cost budget and income budget have a strong categorized relationship with Return on Assets (ROA). This can be seen with an R value of 0.834. (2). Based on the analysis of deviations through the Paired sample t-test technique it is known that the deviations that occur in the income and operational costs budget with its realization are still within the limits of management control. (3). Based on the t-statistical test, it was concluded that partially the operational cost budget and income budget had no significant effect on the Return on Assets (ROA) of PT. AIR Manado. It is recommended that the management of PT. AIR Manado, you should pay attention to the preparation and determination of the operational cost budget and income budget in order to give a greater contribution in the assessment of company performance.Keywods : Operational Budget, Budget Costs Income, Financial Performance